Anomalous luminescence temperature dependence of (In,Ga)(As,Sb)/GaAs/GaP quantum dots overgrown by a thin GaSb capping layer for nanomemory applications - Elisa Maddalena Sala; Petr Klenovský (New Journal of Physics, 2023)
We study (In,Ga)(As,Sb)/GaAs quantum dots (QDs) embedded in a GaP (100) matrix, which are overgrown by a thin GaSb capping layer with variable thickness. QD samples are studied by temperature-dependent photoluminescence, and we observe that the QD emission shows anomalous temperature dependence, i.e. increase of energy with temperature increase from 10 K to ∼70 K, followed by energy decrease for larger temperatures. With the help of fitting of luminescence spectra by Gaussian bands with energies extracted from eight band $k·p$ theory with multiparticle corrections calculated using the configuration interaction method, we explain the anomalous temperature dependence as mixing of momentum direct and indirect exciton states. We also find that the k -indirect electron–hole transition in type-I regime at temperatures ${\lt} 70$ K is optically more intense than k -direct. Furthermore, we identify a band alignment change from type-I to type-II for QDs overgrown by more than one monolayer of GaSb. Finally, we predict the retention time of (In,Ga)(As,Sb)/GaAs/AlP/GaP QDs capped with GaSb layers with varying thickness, for usage as storage units in the QD-Flash nanomemory concept and observe that by using only a 2 ML-thick GaSb capping layer, the projected storage time surpasses the non-volatility limit of ten years.